Surgical audit of inguinal hernia surgery under local anaesthesia at a district hospital set up in central India - Jain, Anurag; Jain, Rajiv; Gupta, Hariom (International Surgery Journal, 2019)
Background: This article outlines the results of audit for feasibility and reliability of use of local anaesthesia as a routine practice in inguinal hernia surgery in an Indian district hospital setup. Through this prospective study an effort have been made to analyse practicability of local anaesthesia for inguinal hernia surgery in terms of cost effectiveness, minimizing recovery period, and reducing routine case load on hospitals with a goal to provide health for all, in a set up where patient load outnumber resources both in expertise and facilities. Methods: A prospective analysis and auditing of 120 patients with unilateral inguinal hernia who underwent inguinal hernia surgery by Lichtenstein tension free mesh repair under local anaesthesia at Sehore district hospital during the study period was done. The primary outcomes of the study were analysed on grounds of cost benefit, patient satisfaction levels, complications such as infection, haematoma, chronic pain, and recurrence. Results: The mean age of patients in present study was 44.23 years (20-76 years). The mean operating time was 70 minutes (40-90). The mean post operative room stay was 3.3 hours (2-6 hours). Intraoperatively 30 patients (25%) had problems such as pain, bradycardia/tachycardia, hypotension, perspiration. Recurrance was observed in 1 patient (0.83%) during the mean follow-up of 3.6 months (1-6 months). Conclusions: In hernia repairs local anaesthetic is reliable, easy, safe and cost effective technique and its use can dramatically reduce waiting period for operation in planned surgeries.